PKM Implementation of Complementary “Cupping” Nursing in Controlling Hypertension During Covid-19 Pandemic - Ahmad Kholid Fauzi; Handono Fatkhur Rahman; Mohammad Alfian Faisol Mustaqim; Fauzan Abdul Latif; Dwiki Qutsi Ali Multazam; Anando Setyo Adiwirawan; Ahmad Labib Umam Musthofa; Badrul Nurul Hisyam (Universitas Nurul Jadid, 2021)
The number of sufferers infected with Covid-19 is increasing in Indonesia. Kompas states that there were 3,874 people infected with Covid-19 as of September 27, 2020. There are 275,213 people infected with Covid-19 to date. This case increase gives special attention to various government and scientific disciplines. Kompas 18 May 2020 stated that based on reports that around 35 % of Covid-19 patients are people with hypertension, diabetes mellitus, and other cardiovascular diseases. This community service staff will implement complementary nursing